Laminaria ochroleuca as a natural remediator of copper-based antifouling agents in aquaculture systems - Cereja, Rui; Pereira, Alícia; Brito, Ana C.; Pires, Carla; Diniz, Mário; Ferreira, Inês; Mil-Homens, Mário; Brito, Pedro; Costa, Pedro Reis; Marques, António (Marine pollution bulletin, 2026)
Fouling is a major challenge for marine aquaculture infrastructures, and copper-based antifouling products are commonly used to address this issue. The wider adoption of multitrophic aquaculture to sustainably produce multiple species is encouraged worldwide, as it promotes nutrient recycling while reducing problems associated with contaminants. In this study, Mytilus sp. and Laminaria ochroleuca were exposed, either individually or in combination, to ropes coated with copper-based antifouling paint. The aim was to evaluate the acute toxicity of Cu in both species, with particular emphasis on Cu accumulation, stress biomarkers, and photosynthetic pigments. The macroalga L. ochroleuca effectively reduced Cu concentrations in the surrounding water. This reduction resulted in increased survival of Mytilus sp. compared to the treatment without macroalgae. In response to Cu exposure, L. ochroleuca exhibited a decrease in chlorophyll a concentration and an increase in the proportion of phaeophytin a relative to chlorophyll a. Higher Cu accumulation led to mortality in L.ochroleuca after 15 days of exposure, whereas Mytilus sp. showed high mortality during the first 7 days. Cu exposure altered stress biomarkers, with increased lipid peroxidation detected in L.ochroleuca tissues and in Mytilus sp. gills. When both species were cultivated together, a less pronounced stress response was observed in both organisms. The reduction in Cu levels in the water and the improved survival of Mytilus sp. in this treatment indicate that L.ochroleuca plays a key role in bioremediation by reducing exposure to Cu-based compounds in shellfish. [Display omitted] •L. ochroleuca reduced waterborne copper and protected mussels;•L. ochroleuca accumulated high copper levels and revealed resilience;•Cu exposure triggered mussel gill degeneration and macroalgae bleaching;•Cu exposure increased lipid peroxidation in both organisms;•IMTA did not improve algal and mussels physiology.